Unveiled magnetic transition in Na battery material: μ+SR study of P2-Na0.5VO2. Issue 24 (15th March 2015) - Sugiyama, Jun; Umegaki, Izumi; Andreica, Daniel; Baines, Christopher; Amato, Alex; Guignard, Marie; Delmas, Claude; Månsson, Martin
<x xml:space="preserve">Abstract</x> Muon-spin spectroscopy has clarified that the magnetic transition occurs not at 13 K but at 2 K in P2-Na0.5VO2.